Validation of an actuator line method for tidal turbine rotors - Wimshurst, A; Willden, R (International Society of Offshore and Polar Engineers, 2016)
Computations of the blade loading and the local flow field around the Model Rotor Experiments In Controlled Conditions (MEXICO) rotor are presented using an actuator line method, implemented within the open source code OpenFOAM. The nacelle and near wake mesh refinement are shown to have little influence on the computed blade loads but a significant impact on the near wake flow field. In addition, the blade loads and near wake flow field calculated with 3 different distributions of the Gaussian smearing parameter ∈ are compared with experimental measurements. Local chord and lift coefficient scaled smearing distributions are shown to yield a significant improvement in the representation of the computed tip vortices and also a small improvement in the blade loading prediction, when compared with a spanwise constant smearing distribution. Despite these improvements in performance prediction, the performance of the rotor is shown to be more strongly influenced by the tip correction factor, where considerable improvement is still required before actuator line methods can represent real rotors with sufficient accuracy.